REKOMENDASI PENJADWALAN PERAWATAN UNTUK MENGURANGI DOWNTIME PADA MESIN GLOSS CALENDAR II DENGAN METODE FMEA & MTBF - Nisa Isrofi; Desita Nur Rachmaniar (KAIZEN : Management Systems & Industrial Engineering Journal, 2022)
PT ABC is a company that produces pulp and paper. The company works 24 hours and each machine is a continuous process. A reliable production system is important so that machines and other components can operate without being damaged during production. The problem is the damage that occurs at any time before the maintenance interval so it needs corrective maintenance. This research is limited to the gloss calendar II machine. To avoid corrective maintenance, optimal preventive maintenance actions are needed by determining maintenance intervals. This study aims to schedule preventive maintenance that minimizes downtime in the gloss calender II using MTBF and FMEA. After analyzing the causes of failure, an assessment and ranking of each cause of failure are carried out according to the severity and frequency of occurrence. The methods used are Failure Modes and Effects Analysis (FMEA) and Mean Time Between Failures (MTBF). FMEA is a structured analysis method to identify and analyze various failure modes that occur in components, while MTBF is a method to find maintenance intervals. The result of this paper is a proposal for an ideal preventive maintenance time interval to reduce downtime on a gloss calendar machine using the FMEA & MTBF method.